2018
DOI: 10.15252/embj.201798321
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of membrane pore formation by human gasdermin‐D

Abstract: Gasdermin‐D (GSDMD), a member of the gasdermin protein family, mediates pyroptosis in human and murine cells. Cleaved by inflammatory caspases, GSDMD inserts its N‐terminal domain (GSDMDNterm) into cellular membranes and assembles large oligomeric complexes permeabilizing the membrane. So far, the mechanisms of GSDMDNterm insertion, oligomerization, and pore formation are poorly understood. Here, we apply high‐resolution (≤ 2 nm) atomic force microscopy (AFM) to describe how GSDMDNterm inserts and assembles in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
182
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(193 citation statements)
references
References 44 publications
11
182
0
Order By: Relevance
“…Studies focusing on GSDMD have reported 16 protomer-shaped pores with inner diameters of 12–14 nm (Aglietti et al, 2016; Ding et al, 2016; Liu et al, 2016; Sborgi et al, 2016); however, these studies have not examined the crystal structure of GSDMD. In contrast, studies by Sborgi et al (2016) and Mulvihill et al (2018) showed that GSDMD pores could instead be averaging ∼20 nm, closer to the diameter of the GSDMA3 pore.…”
Section: Pore Formation As a Means Of Cytokine Release And Cell Deathmentioning
confidence: 82%
“…Studies focusing on GSDMD have reported 16 protomer-shaped pores with inner diameters of 12–14 nm (Aglietti et al, 2016; Ding et al, 2016; Liu et al, 2016; Sborgi et al, 2016); however, these studies have not examined the crystal structure of GSDMD. In contrast, studies by Sborgi et al (2016) and Mulvihill et al (2018) showed that GSDMD pores could instead be averaging ∼20 nm, closer to the diameter of the GSDMA3 pore.…”
Section: Pore Formation As a Means Of Cytokine Release And Cell Deathmentioning
confidence: 82%
“…Consistent with the description of these two distinct kinetic steps, the vast majority of end-point MACs in our data are complete, ring-shaped pores. If the rate of initial C9 insertion were faster than the subsequent oligomerization reaction, kinetically-trapped, arc-shaped assemblies would occur due to monomer depletion, as has been observed for other pore-forming proteins 27,28,31 . To determine whether the kinetic bottleneck is attributed to C8 incorporation or insertion of the first C9, we allowed an extended temporal window after the addition of C8 and prior to adding C9 (SI Fig.…”
Section: Initial Insertion Of C9 Is a Kinetic Bottleneck In Mac Assemblymentioning
confidence: 87%
“…The findings made by Mulvihill et al provide detailed mechanistic insights into transmembrane pore assembly by GSDMD Nterm . Given the conserved pore‐forming activity in the entire gasdermin family, the Mulvihill study (Mulvihill et al , ), together with the recently determined Cryo‐EM structure of GSDMA3 pores (Ruan et al , ), builds an elegant framework for understanding membrane pore formation during other gasdermin‐mediated pyroptosis that are associated with diverse pathophysiological processes.…”
Section: Schematic Of the Gsdmdnterm Pore Formation Processmentioning
confidence: 99%
“…family, the Mulvihill study (Mulvihill et al, 2018), together with the recently determined Cryo-EM structure of GSDMA3 pores (Ruan et al, 2018), builds an elegant framework for understanding membrane pore formation during other gasdermin-mediated pyroptosis that are associated with diverse pathophysiological processes.…”
mentioning
confidence: 99%